A specific isoform of Pyd/ZO-1 mediates junctional remodeling and formation of slit diaphragms - Carrasco-Rando, Marta (J Cell Biol, 2019)
The podocyte slit diaphragm (SD), responsible for blood filtration in vertebrates, is a major target of injury in chronic kidney disease. The damage includes severe morphological changes with destabilization of SDs and their replacement by junctional complexes between abnormally broadened foot processes. In Drosophila melanogaster, SDs are present in nephrocytes, which filter the fly's hemolymph. Here, we show that a specific isoform of Polychaetoid/ZO-1, Pyd-P, is essential for Drosophila SDs, since, in pyd mutants devoid of Pyd-P, SDs do not form and the SD component Dumbfounded accumulates at ectopic septate-like junctions between abnormally aggregated nephrocytes. Reintroduction of Pyd-P leads to junctional remodeling and their progressive normalization toward SDs. This transition requires the coiled-coil domain of Pyd-P and implies formation of nonclathrin vesicles containing SD components and their trafficking to the nephrocyte external membrane, where SDs assemble. Analyses in zebrafish suggest a conserved role for Tjp1a/ZO-1 in promoting junctional remodeling in podocytes.